Theoretical study of bacteriochlorophyll aggregates using methods of quantum chemistry and molecular mechanics - Ninou-Codina, Marc (Jihočeská univerzita, 2020)
This bachelor thesis is focused on the theoretical study of bacteriochlorophyll aggregates. Bacteriochlorophyll (BChl) is a photosynthetic pigment found in light-harvesting antenna systems called chlorosomes. It has been found, that in chlorosomes these aggregates have a lamellar nature, and form distinct curvature. The aim of the thesis was to attempt to identify the origin of curvature formation in chlorosomes aggregates from a local energy perspective, by geometrically optimizing the system and calculating the local interaction energy of tetramer structures located in different sections of BChl aggregates employing different methods of computational chemistry. The results suggest that curvature does not originate from local interactions.
Theoretical study of bacteriochlorophyll aggregates using methods of quantum chemistry and molecular mechanics